DISASTER RECOVERY THROUGH PREDICTION OF SAFE ROUTE USING DEM LEVELS - Vp, Sangavi; N, MOUNIKA; N, GRACELINE JASMINE (Asian Journal of Pharmaceutical and Clinical Research, 2017)
When a disaster occurs, the normal commutation routes are disrupted. People get stuck at these disaster points and would be in trouble, hence people in those areas find it difficult to communicate and evacuation route to safe area is unknown. The aim of the paper is to predict safe routes to reach the refuge point from the disaster point. The prototype was developed using Arc geographic information system runtime SDK for Java Application and APIs in Eclipse. The system was developed with digital elevation model layer, and route layer for India basemap focused to Tamil Nadu. The safe route is found based on the elevation values of the area from the disaster point to a safe point. The developed system could be used by the relief providers to reach the disaster point and rescue victims.